Sosialisasi Pentingnya Sport Massage Pada Mahasiswa Pendidikan Jasmani Sebagai Peluang Usaha - Parengkuan, Meyke; Mile, Rifky; Pakaya, Rosbin (Jambura Arena Pengabdian, 2024)
The socialization of sports massage among students aims to improve their understanding and skills in maintaining body health, especially in physical activities and sports. This activity involves delivering theory, demonstrating techniques, and direct practice with the guidance of professional practitioners. This community service activity is important considering the high need for students for insight into fitness and physical recovery techniques, as well as the potential of sports massage as a business opportunity. Through this activity, students not only gain health benefits, but also the opportunity to develop skills that can be applied practically in everyday life or to support economic independence. The method of implementing the activity includes delivering theory about the basic concepts of sports massage, demonstrating techniques by professional practitioners, and direct practice that actively involves participants. Evaluation is carried out using pre-tests and post-tests to measure increased understanding, as well as direct observation during practice to assess mastery of techniques. The evaluation results show an increase in participants' understanding of the benefits and techniques of sports massage, as well as enthusiasm to practice it independently. However, there are suggestions to extend the duration of practice to deepen skills. With a comprehensive approach, this socialization is expected to have a positive impact on students, both individually and on the campus community.